Comparing short-term risk of repeat self-harm after psychosocial assessment of patients who self-harm by psychiatrists or psychiatric nurses in a general hospital: cohort study - Pitman, A; Tsiachristas, A; Casey, D; Geulayov, G; Brand, F; Bale, E; Hawton, K (Elsevier, 2020)
Background: There is mixed evidence for whether psychosocial assessment following hospital presentation for selfharm reduces self-harm repetition. A possible reason is the differences in professional background of assessors (primarily psychiatrists and psychiatric nurses) due to variability in training and therapist style.